Transport properties and pore‐network structure in variably‐saturated Sphagnum peat soil. (15th December 2015) - Hamamoto, S.; Dissanayaka, S. H.; Kawamoto, K.; Nagata, O.; Komtatsu, T.; Moldrup, P.
Summary: Gas and water transport in peat soil are of increasing interest because of their potentially large environmental and climatic effects under different types of land use. In this research, the water retention curve (WRC), gas diffusion coefficient ( D g ) and air and water permeabilities ( k a and k w ) of layers in peat soil from two profiles were measured under different moisture conditions. A two‐region Archie's Law (2RAL)‐type model was applied successfully to the four properties; the reference point was taken at −9.8 kPa of soil‐water matric potential where volume shrinkage typically started to occur. For WRC in the very decomposed peat soil, the 2RAL saturation exponents ( n ) obtained for both the wetter ( n w ) and drier regions ( n d ) were smaller than those for the less decomposed peat. For Dg, the saturation exponent in the wetter region was larger than that in the drier one for all layers, which indicated enhanced blocking effects of water on gas diffusion in the wetter region. For the peat layers within each soil, there was a linear relation between saturation exponents in the drier region for k a and D g . The larger saturation exponent of the wetter region for k w in peat than in sand suggests a need for specific hydraulic functions for peat soil. The 2RAL model for D g agreed well with measured data, and performed better than existing unimodal models. To facilitate use of the 2RAL for D g, we developed a simple predictive expression for D g at the reference point. The pore‐network tortuosity factor and equivalent pore diameter for gas transport confirmed very different pore structure and mass transport behaviour for peat soil and uniform sand.